The Political Carousel Elite Powersharing, Political Instability and the Allocation of Senior Government Posts in Africa - Wigmore-Shepherd, Daniel (2019)
"This research project examines how various political events and factors influence the composition of senior government elites in a range of African states. Using a newly created dataset of African cabinet ministers, this thesis creates a number of metrics to measure elite volatility and ethnic, regional and political representation. These metrics are used to assess leader and regime strategies of elite power-sharing. It then employs a range of quantitative and qualitative methods to investigate how factors such as ethnic demography, regime strength, economic performance, opposition cohesion and popular unrest influence these metrics. Through this process the thesis aims to demonstrate how the distribution of political power within a state can be estimated by allocation and reshuffling of cabinet ministers. This research project contributes a number of key findings. Firstly, most regimes represent the majority relevant subnational groups within the senior government, but that representation is unbalanced with certain groups being overrepresented and others underrepresented. Secondly, these imbalances and variation in which groups are favoured provide information on the distribution of political power. Thirdly, that different political environments lend themselves to different compositions in the senior government and different strategies of elite power-sharing. In the same vein, individual political events which alter the balance of power are accompanied with corresponding changes in senior government which reflect these shifts in the political hierarchy. These findings contribute to the debates on the determinants of African political power distributions, elite designations and processes, formal vs informal institutions and the political survival literature. A broad benefit of this work is to demonstrate the variance in power sharing arrangements across the African continent. Furthermore, this project demonstrates that external events change leader and elite calculations, which in turn changes strategies of power sharing."